The circulation of the Mediterranean Sea: a historical review of experimental investigations - A. Bergamasco; P. Malanotte-Rizzoli (Advances in Oceanography and Limnology, 2010)
The Mediterranean Sea is an enclosed basin composed of two similar basins and different sub-basins. It is a concentration basin, where evaporation exceeds precipitation. In the surface layer there is an inflow of Atlantic water which is modified along its path to the Eastern basin. This transformation occurs through surface heat loss and evaporation specifically in the Levantine basin. The Mediterranean is furthermore the site of water mass formation processes, which can be studied experimentally because of their easy accessibility. There are two main reasons why the Mediterranean is important. The first one is the impact of the Mediterranean on the global thermohaline circulation, the second reason is that the Mediterranean basin can be considered as Laborartory for investigating processes occurring on the global scale of the world ocean. In this paper we want to provide a short historical review of the evolving knowledge of the Mediterranean circulation that has emerged from experimental investigations over the last decades. We start by describing the old picture of the basin circulation which had stationary, smooth large scale patterns. Then we show the major experiments that led to the discovery of the sub-basin scale circulation and its mesoscale features. We conclude with the dynamical discovery of EMT in the 1990s and the most exciting ongoing new research programmes.